Baseline study of heavy metal pollution in a tropical river in a developing country - Tengku Nilam Baizura Tengku Ibrahim,; Faridah Othman,; Noor Zalina Mahmood, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Massive load of toxic heavy metals is discharged by human activities, as well as by natural actions, give rise to metal contamination in water body. Sg. Sembilang is one of the rivers that is receiving effluent from various sources such as landfill, industrial, residential, and agricultural runoff. In this study, the concentration of heavy metals in nine stations along the Sg. Sembilang was collected for one year period to evaluate their levels of pollution. Ten heavy metals were analyzed using inductively coupled plasma optical emission spectroscopy (ICP-OES). The mean concentrations of Fe, Mn, Zn, Al, and Cu were 3.01, 0.68, 0.29, 0.007, and 0.027 mg/L respectively, were below the National Water Quality Standards of Malaysia (NWQS), with the exception of Cd, Cr, Pb, Mg, and Ni. Calculated HPI based on the mean concentration of heavy metals, was found to be 6.05, that is below the critical pollution index value of 100. With respect to sampling locations, station J03 registered the highest value of 7.989. This is probably due to the location of J03 which is very near to the effluent discharge point. The analysis indicates the present scenario of water quality of Sg. Sembilang due to the effect of effluent from the landfill material, and waste water from industry, agricultural runoff and residential area. Required steps should be taken to conserve this river from pollution, and also to lessen the environmental risk.